Case report: Episodic psychosis caused by a novel SCP2 splicing mutation - Tang, Haiyan; Luo, Yingying; Tang, Zhenchu; Tang, Jianguang; Fang, Jia (Frontiers in Neurology, 2023)
SCPx deficiency is a rare disorder of peroxisomal beta-oxidation dysfunction, and it has only been documented in two patients thus far. In the previously reported patients, both patients were primarily presented with slowly progressive dystonia or ataxia, and they both displayed symmetrical lesions in the thalamus and brainstem on magnetic resonance imaging. This study presents the third patient exhibiting a similar neuroimaging abnormality but a notably different clinical phenotype characterized by episodic psychosis. Through whole-exome sequencing, we identified a homozygous splicing mutation in SCP2 (c.674 + 1G > C), and further RNA sequencing revealed exon 8 skipping in the mature transcripts of SCP2. This study significantly expands our understanding of the genotypic and phenotypic spectrum associated with SCP2-related metabolic encephalopathy.